Specifying the Methods to Calculate Thermal Efficiency of a Dual Production Well System "Fluid-Geoheat" - Fyk, M. I.; Biletskyi, V. S.; Abbood, M.; Desna, N. A. (My University, 2022)
Methods to calculate thermal efficiency of dual production well system “fluid-geoheat” have been specified for conditionally thin productive fluid-saturated seam in terms of radial planar filtration. It has been demonstrated that relative to a variant, ignoring Joule-Thompson effect, and variant of discrete Joule–Thomson coefficient substitution, calculation accuracy as for the well heat efficiency increases by 33% and 9% respectively. It has been proved that it is expedient for a conditionally thin seam to use effective temperature within the heat-exchange equitation with Fourier substitution as related to heat transfer while considering heat input in terms of unidirectional input to a virtual disk plate from the seam floor. In the context of the proposed calculation methods, increase in numerical estimations of thermal efficiency of a well results from the consideration of extra heat pumping owing to Joule-Thompson effect by rocks adjoining the productive formation.
Keywords: hydrocarbon well; thermal efficiency of a system; mechanocaloric effect; thermal diffusion; geothermal energy production